RUANG BERMAIN MERUPAKAN RUANG BELAJAR: MANAJEMEN SARPRAS PAUD BERBASIS KEAMANAN DAN KREATIVITAS (KONSEP : FOKUS PADA BAGAIMANA MENGELOLA ASET SEKOLAH AGAR SESUAI DENGAN STANDAR NASIOLAN SEPERTI PERMENDIKBUD) - Niya Ramadona, Suci; Fadhilah Hasanah, Dinah; Putri, Nasya; Meisari, Erika; Fahmi , Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the management of early childhood education (PAUD) facilities and infrastructure (sarpras) based on safety and creativity, with reference to national education standards, specifically the Ministry of Education and Culture regulation on PAUD facility standards. The concept of "Play Space is Learning Space" is used as a basis, emphasizing that children's play environments must be safe, comfortable, and stimulate creativity and early learning development. A descriptive qualitative approach is applied through observation, interviews, and documentation in PAUD institutions. The results reveal that PAUD facility management does not fully meet the standards, especially in terms of safety and space arrangement. However, the application of creative and safe facilities has been proven to improve the quality of learning and the optimal development of children. It is concluded that safety- and creativity-based PAUD facility management is essential to create a conducive learning environment.